BIM Deletion Polymorphism Profiling Complements Prognostic Values of Risk Scores in Imatinib-treated Asian Chronic Myeloid Leukemia Patients - Hein Than (Taylor & Francis, 2019)
10.1080/10428194.2018.1461863